Efficacy of Vaccination against Eimeria spp. in poultry (Research, Society and Development, 2022)
Eimeriosis represents a considerable challenge faced by the global poultry industry due to the damage it causes. Three species of Eimeria in chickens, in this case, E. acervulina, E.max and E. tenella have the potential to affect the occurrence and extent of resistance to anticoccidial drugs and future vaccines. Thus, it is clear that vaccination against avian eimeriosis has an important role in maintaining biosafety and productivity in poultry breeding, since in addition to providing the immunization of animals, it helps in increasing the therapeutic efficiency of anticoccidial drugs. In this study, we investigated the effectiveness of vaccination against eimeriosis in broiler birds. In total, 589 articles were compiled in research databases and scientific publications. As a filter to avoid duplication between works, 62 articles were obtained. Of these, in only five did we observe a very high degree of recommendation for the use of DNA vaccination, which was considered more effective in preventing eimeriosis, with a lower degree of side effects.